Heart transplantation in two adolescents with Danon disease. (7th December 2018) - Oren, Daniel; Chau, Peter; Manning, Melanie; Kwong, Joann; Kaufman, Beth D.; Maeda, Katsuhide; Rosenthal, David N.; Hollander, Seth A.
Abstract: Danon disease (DD) is an X‐linked dominant disorder caused by a mutation in the lysosomal‐associated membrane protein‐2 (LAMP‐2) gene coding for the LAMP‐2 protein. We report two cases of successful heart transplantation (HT) in adolescent brothers with DD, including one who was bridged to HT for 34 days with a HeartWare left ventricular assist device. In both patients, the post‐transplant course was complicated by profound skeletal muscle weakness that resolved with corticosteroid withdrawal. These cases highlight that both HT and ventricular assist device support are feasible in patients with DD. Corticosteroid use may exacerbate skeletal myopathy, and therefore, steroid minimization may be warranted whenever possible.